A Study of impact on English language skill using content and language integrated learning approach adopting blended teaching - Banick, Pratima Rani; Subbaih, Soundiraraj (Research Journal in Advanced Humanities, 2025)
The current research aims to study language learning skill enrichment impact on EFL/ESL learners through the use of Content and Language Integrated Learning (CLIL) approach adopting blended teaching. With education shifting from knowledge acquisition to competency-based learning, and the post-pandemic demands of teaching online becoming a norm, a contextually relevant language teaching approach at school level has become necessary to investigate. In the current study, blended teaching denotes a combination of physical mode and the live online or web-based technology tools used teaching. Likewise, CLIL denotes content integrated language learning where content of various academic disciplines is used as teaching resource to provide the cognitive load, to achieve the objective language skill in English language Teaching (ELT). The quantitative study includes two groups (n=25) experimental group and (n=25) controlled group with the heterogenous mix of boys and girls of 15-16 years age selected from an online English School of India. The selected student sample had exposure to English language learning in an academic setting for at least ten years in the international curriculum prior to study. The results of the study are measured analysing the data of student’s pre-test, post-test and the delayed post-test conducted before, during and after the treatment respectively. For comprehending the attitude towards learning, a survey questionnaire has been used. The results demonstrate the performance of the experimental group in language skill development and maturity in thoughts has incremental improvement when compared to the conventional teaching of form focused language skill acquisition in the physical setting.